PENGARUH KOMITMEN KERJA, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Batu) - Muhammad Naufal Nur H; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The purpose of this study is to describe work commitment, work motivation, and job satisfaction, and employee performance at the Batu City Human Resources and Human Resources Development Agency and to investigate whether work commitment, work motivation, and job satisfaction simultaneously and partially affect employee performance Batu City Human Resources and Human Resources Development Agency or not. This study involved 51 of 51 employees as a sample. The sampling technique is saturated sample, which considers all elements or categories in the population to be selected as a sample. The instrument used was a questionnaire and document analysis. Then, the data were analyzed using descriptive statistics and multiple linear regression analysis. The results showed that (1) work commitment, work motivation and job satisfaction simultaneously affect employee performance, (2) work commitment has a positive and significant effect on employee performance, (3) work motivation has a positive and significant effect on employee performance, and (4) job satisfaction has a positive and significant effect on employee performance.Keywords: work commitment, work motivation, job satisfaction.